Electro-discharge machining for non-metal based fabrication process - Saleh, Tanveer (Nova Publishers, 2015)
Machining is a regulated material removal process from a piece of raw material which can be divided into mainly two major groups “Conventional Machining Processes” and “Non-Conventional Machining Processes”. Turning, boring, milling, shaping, broaching, slotting, grinding etc fall under the category of conventional machining processes. Similarly there are several examples of non-conventional machining such as Abrasive Jet Machining (AJM), Electro-chemical Machining (ECM) and Ultrasonic Machining (USM) etc. Electro-Discharge Machining/ Wire Electro-Discharge Machining are other nonconventional machining technology which is extensively used for metal based fabrication process. Electro-discharge machining (EDM) makes use of electrical energy to transform into thermal energy. This process enables machining of any material, which is electrically conductive, irrespective of its brittleness, hardness or strength. The basic principle of this machining type is when the material of the workpiece is removed through high frequency sparks between the tool and the workpiece immersed into the dielectric fluid like oil, de-ionized water etc. Wire electro-discharges machining (WEDM) is a variant of EDM based method for non-contact machining using wire as the machining tool. When very low energy (in µ-joule range) is used for creating these sparks, the process is called as µ-WEDM. Silicon (Si) is an important engineering material that is used mostly in Electronics and MEMS (Micro Electro-Mechanical System) based applications. As mentioned above EDM/WEDM technology is mainly used for metal based fabrication process however, in recent times researchers are using this method for non-metal based machining processes like Vertically Aligned Carbon Nanotube, Carbon Nanotube Composite, Conductive Polymer, Ceramics and Semiconductor materials. This chapter will discuss about the application of EDM/WEDM technology for nonmetal based machining both in macro and micro domain.